Elaboração e implementação de um plano de manutenção em uma indústria farmacêutica do Rio Grande do Norte - Faria, Edália Azevedo de (2018)
The phenomenon of globalization has increased the diversity among industries. Consequently, industries have invested more and more in production strategies, among the main ones, in the maintenance area. The maintenance industry must be competitive and ensure the availability of equipment and facilities to increase productivity with quality. Thus, this work has the objective of elaborating maintenance planning and its implementation by means of a maintenance plan in a pharmaceutical industry in the city of Natal, Rio Grande do Norte. The need for the restructuring of the engineering and maintenance sector was due to the reform of the productive sector to produce a new line of medicines. It was decided, together with the management of the factory and after a study of the reality of the factory, to always prioritize the availability of equipment, through planning and execution of preventive and corrective maintenance, reducing unwanted stops that could decrease competitiveness and generate losses. Thus, a methodology focused on the organization was prepared and control of the maintenance that best suited the reality of the factory. The execution of this methodology took place through four main steps as key points for an efficient maintenance management. All proposals were successfully implemented, so the purposes of this work were achieved.